‘iTIME’ AS A BLESSING OR A CURSE: IMAGINARIES OF SMARTPHONE USE AND PERSONAL AND SOCIAL TIME AMONG GENERATION GROUPS IN ESTONIA - Kalmus, Veronika (AoIR Selected Papers of Internet Research, 2015)
The paper employs data from the 5th round of the representative population survey ‘Me. The World. The Media’ (N=1,500), gathered at the end of 2014 in Estonia. The post- socialist transition in Estonia has been described as extremely radical, characterized by highly liberal transformation policies and economic reforms, and rapid technological changes. The speed of the diffusion of new information and communication technologies, however, has affected different social groups to a varying degree. As generations differ, due to dissimilar locations on life span, in their speed of adapting to rapid social changes, age has become one of the most significant markers of social and digital stratification (Kalmus, Talves & Pruulmann-Vengerfeldt 2013). In this context, inter-generational differences in time as resource and commodity, time management, and control over one’s time are especially meaningful.